Design and Development Web-Based Information System of Student Attendance in Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Miftahul Ulum - Agus Sunandar, Muhamad; Sri Andar Muni, Lise; Andayani Komara, Mutiara; Pratiwi, Muthia (RISTEC : Research in Information Systems and Technology, 2024)
As time goes by technological progress occurs so rapidly that it helps us in various ways. One of them is creating an information system that can help us in processing data. In the world of education, such as at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Miftahul Ulum, we also need a system that can help in entering data such as student data and attendance data to make it easier for teachers or staff to manage data. Therefore, an attendance information system is needed that allows managing attendance data and other data in an orderly manner to minimize the occurrence of data loss or incorrect data entry and can process the required reports. This research was created using the waterfall method using the PHP programming language by utilizing the Laravel framework as the system display, the MySQL database as data storage, and the Unified Modeling Language (UML) as the system design